Protection against Incidences of Serious Cardiovascular Events Study with daily fish oil supplementation in dialysis patients (PISCES): protocol for a randomised controlled trial - Kevan Polkinghorne; Brenda R Hemmelgarn; Marcello Tonelli; George Tomlinson; Charmaine E Lok; Louise M Moist (BMJ Open)
Introduction Patients with kidney failure with replacement therapy (KFRT) suffer premature cardiovascular (CV) mortality and events with few proven pharmacological interventions. Omega-3 polyunsaturated essential fatty acids (n-3 PUFAs) are associated with a reduced risk of CV events and death in non-dialysis patients and in patients with established CV disease but n-3 PUFAs have not been evaluated in the high risk KFRT patient population.Methods and analysis This multicentre randomised, placebo controlled, parallel pragmatic clinical trial tests the hypothesis that oral supplementation with n-3 PUFA, when added to usual care, leads to a reduction in the rate of serious CV events in haemodialysis patients when compared with usual care plus matching placebo. A target sample size of 1100 KFRT patients will be recruited from 26 dialysis units in Canada and Australia and randomised to n-3 PUFA or matched placebo in a 1:1 ratio with an expected intervention period of at least 3.5 years. The primary outcome to be analysed and compared between intervention groups is the rate of all, not just the first, serious CV events which include sudden and non-sudden cardiac death, fatal and non-fatal myocardial infarction, stroke, and peripheral vascular disease events.Ethics and dissemination This study has been approved by all institutional ethics review boards involved in the study. Participants could only be enrolled following informed written consent. Results will be published in peer-reviewed journals and presented at scientific and clinical conferences.Trial registration number ISRCTN00691795